(untitled) (Research, Society and Development, 2021)
Caryocar coriaceum Wittm., a fruit species, is native and endemic to the Brazilian cerrado, widely used both in the food and medicine industry. This study was aimed carried out a scientific and technological forecasting of C. coriaceum using analysis of both scientific papers and patents indexed in national (INPI) and international (WEB OF SCIENCE, EPO and DII) databases. In total, 29 papers were registered and analyzed in the Web of Science, being 2011, 2015 and 2020 the years with the highest number of publications (n = 4, each). With regard to technological prospecting, the number of filed patents found was considered low (n = 7), when compared to other species of the same genus, for example, Caryocar brasiliense Cambess (n = 57). The EPO was the database with the largest patent registration (n = 4). In it, Brazil is the main depositor country with emphasis on medical and cosmetological purposes. These results suggest that, currently, the interest in the species’ potential is strictly Brazilian and that the scientific and technological development of the species is still growing slowly, which highlights a need for a greater incentive to production and technological innovations with this species.